INDUCTION TRAINING AND EMPLOYEE PERFORMANCE: A STUDY OF NIGERIA DEPOSIT INSURANCE CORPORATION - Ummul-Khairi Mohammed (International Studies Journal)
Despite the reported importance of induction training on the performance of employees, there are extremely very few studies that have examined the effect of induction training on the performance of employees. Therefore, to fill this knowledge gap, this research empirically investigated the influence of induction training on employees' performance of the Nigeria Deposit Insurance Corporation (NDIC). A total of 166 people were selected from a pool of 301 NDIC workers. Simple random sampling was used to choose the study's participants. Employees were chosen at random from a list of names in a basket to serve as research participants. Data acquired for the study were examined on SPPS utilising structural equation modelling using SmartPls2. Based on the empirical analysis of the investigation, all of the null hypotheses of the study were not refuted. As a result, the NDIC's induction training programme, on-the-job training, and delivery system all have a beneficial impact on employee performance. As a consequence, the study demonstrated that the systematic method in which employee training is constructed has an influence on how employees perform. Similarly, frequent on-the-job training ensures that employees perform effectively, and the method in which training is offered has a considerable impact on employee performance. As a result, the study's findings suggest that training should be systematic in order to improve employee performance.